Anatomic characterization of the nasopalatine canal through cone beam computed tomography in a Peruvian population - Obando Castillo, Jorge Luis (2020)
Nasopalatine Canal (NPC) is an important structure that may be susceptible to damage during surgical procedures in the anterior maxilla, therefore a thorough examination of the anatomy and variants of the NPC is imperative for a good diagnosis and an appropriate treatment plan. Objective: To perform an anatomic characterization of NPC using Computed Beam Computed Tomography (CBCT). Material and methods: 154 images of CBCT were evaluated, in which the NPC was analyzed in terms of length, shape, and inclination with respect to the hard palate and the maximum anteroposterior of the incisive foramen (IF) in men and women of 18 years of age and onwards. Results: to the evaluation of the NCP in sagittal slices of CBCT, it presented diﬀerent forms, it was found to the cylindrical shape as the most common in 89 patients (58%), followed by the funnel shape in 38 (25%), and the less frequent were the shape of hourglass in 20 (13%) and spindle (5%). The average length of the NCP was 10.83 mm (± 2.13), the average of the anteroposterior diameter of the FI was 3.44 mm (± 0.80) and the average angulation of the CNP in relation to the hard palate was 16.44 ° (± 7.32). Conclusions: The study showed the variability of NCP in the Peruvian population, like in shape, length and inclination, as well as the diameter of the FI.